THE IMPORTANCE OF DEVELOPING ERROR ANALYSIS SKILLS FOR FUTURE GERMAN LANGUAGE TEACHERS (Scientific journal of the Fergana State University, 2024)
The importance of forming error analysis skills of future German language teachers is investigated in the article. The ability to analyze errors made by language learners is analyzed as an integral part of improving the error-correcting competence of future German language teachers. Some methods of error analysis are described.